2011
DOI: 10.1002/j.2161-1912.2011.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Target Person Expression on Ethnic Prejudice Toward Middle Easterners and Hispanics

Abstract: Research on implicit prejudice suggests that target person judgments may be affected by unintentional, but well-learned, cognitive associations. Ethnicity, gender, and smiling or nonsmiling expression were varied as cues in White college students' perception tasks. The results of a factorial experiment are included as well as a discussion of the implications.La investigación sobre prejuicios implícitos sugiere que los juicios del individuo en cuestión pueden ser afectados por asociaciones cognitivas involuntar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 28 publications
(37 reference statements)
1
10
1
Order By: Relevance
“…Counselors and researchers should also explore possible moderator and mediator variables that likely affect emotional expression and the interpretation of expressions, such as language switching (Ramos‐Sánchez, 2007), levels of client acculturation and enculturation (Nghe, Mahalik, & Lowe, 2003; Wong et al, 2009), and implicit bias (Sullivan, Scott, & Nocks, 2011). For example, further understanding of how immigrants adapt to new CDR systems would be highly valuable when developing interventions that respect clients’ cultural norms and help them adapt to a different set of norms and when informing systems (e.g., universities, schools) of how to be more inclusive of a wider range of emotional expression norms.…”
Section: Discussionmentioning
confidence: 99%
“…Counselors and researchers should also explore possible moderator and mediator variables that likely affect emotional expression and the interpretation of expressions, such as language switching (Ramos‐Sánchez, 2007), levels of client acculturation and enculturation (Nghe, Mahalik, & Lowe, 2003; Wong et al, 2009), and implicit bias (Sullivan, Scott, & Nocks, 2011). For example, further understanding of how immigrants adapt to new CDR systems would be highly valuable when developing interventions that respect clients’ cultural norms and help them adapt to a different set of norms and when informing systems (e.g., universities, schools) of how to be more inclusive of a wider range of emotional expression norms.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) found that the “model minority” characterization of Asian-Americans may also elicit perceptions of low warmth. Although these stereotypes of high competence and low warmth would seem to suggest that Asian targets would be rated less approachable compared to White targets, previous studies involving these target groups have not found a main effect of target race/ethnicity for ratings of threat (Sullivan et al., 2011) or extraversion and agreeableness (Tsai et al., 2019). In light of the results found by Sullivan et al.…”
Section: Introductionmentioning
confidence: 86%
“…Because people’s judgments of others can be influenced by qualities of the targets as well as their own characteristics (e.g., Shapiro et al., 2009; Sullivan et al., 2011; Xie et al., 2019; Zebrowitz et al., 1993), the current research examined this potential target × perceiver interaction on face evaluations through two studies. Study 1 used a between-subjects design in which participants assessed several targets of only one ethnicity (Black, East Asian, or White) and displaying the same facial expression (either smiling or a neutral expression).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations